Çerçevesinde Matlab/Simulink ile İncelenmesi [Asenkron Motorlarin DQ Eksende Üç Referans] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
Mathematical modeling of the dynamic behavior of the asynchronous motor and simulation of this model with simulation programs play an important role in applications regarding both, the cost reduction and time-saving for the control, design and analysis of errors and malfunctions in the motor. Literature research reveals that most researchers have adopted only one reference framework to estimate the machine's transient behavior. In this article, modeling with qd0 axis-based MATLAB / SIMULINK was studied to analyze the transient performance of the three-phase squirrel cage induction motor using stator reference frame, rotor reference frame and synchronously rotating reference frame. In addition, a MATLAB/SIMULINK/GUI application has been created through integrating the MATLAB/SIMULINK model of the asynchronous motor with the MATLAB/GUI to examine the effect of the motor parameters on the dynamic behavior of the motor. © 2020 IEEE.
Keywords: Asynchronous motor; Dq0 reference theory; Matlab GUI; MATLAB/SIMULINK